Dampak Konflik Agraria Terhadap Kepercayaan Politik Petani Di Sumatera Utara - Anshari, Andry; Amin, Muryanto; Situmorang, Tonny P (PERSPEKTIF, 2024)
This paper aims to analyze the impact of agrarian conflicts on the political trust of peasants who are victims of agrarian conflict in North Sumatra. The study utilizes political trust theory and agrarian conflict as analytical tools with a qualitative approach. Political trust serves as the foundation of the relationship between society and the state, shaped by the government's performance in policy or conflict resolution, such as agrarian conflicts. Agrarian conflicts typically manifest through actions like land grabbing, the unilateral takeover of land by companies, the exploitation of natural resources for economic gain, leading to the displacement of traditional peasants, and violations of peasants' rights, such as criminalization or distancing peasants from agrarian sources. The research results indicate that agrarian conflicts have influenced the political trust of peasants due to the lack of clarity in enforcing agrarian conflict resolution rules, the unfair distribution of resources, and the unequal opportunity for peasants to access justice.